Applying the SWAN model to predict wave fields in Hai Phong coastal area - Cuong, Le Duc (Vietnam Journal of Marine Science and Technology, 2019)
This paper presents some results of studying the SWAN model, and application of SWAN model to simulate wave field representative of the rainy season and dry season in the coastal area of Hai Phong. During the dry season, the dominant wave direction is in a range from 60o to 100o, maximum height of waves near shore is in a range from 1,0 m to 1,5 m with wavelength of about 2,0 m to 5,0 m, maximum height of waves offshore is in a range from 2,0 m to 2,5 m with wavelength of about 6,0 m to 16 m. During the rainy season, wave height near shore is in a range from 0,2 m to 0,6 m, and that offshore is in a range from 0,8 m to 1,4 m, maximum height of waves is about 3,4 m, predominant wave directions in this season are E, SE and S. In this scenario that predicts waves generated by storms, wave height offshore is in a range from 8,0 m to 10 m with wavelength of about 60 m, and that near shore is in a range from 2,0 m to 4,0 m with wavelength of about 10–20 m.